2016
DOI: 10.1111/ijcp.12777
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of diabetic ketoacidosis in Arab patients with type 1 diabetes: a systematic review

Abstract: Aims: Diabetic ketoacidosis (DKA) is an acute and risky complication of type 1 diabetes. The aim of this study is to build the overall rate of DKA in Arab patients with type 1 diabetes in the 22 Arab nations. This is expected to tailor the healthcare approaches in Arab countries where attention is needed to save lives from the devastating consequences of DKA. Methods: The study here is a quantitative analysis of the articles indexed in four different scientific literature databases: Web of Science, PubMed, Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
2
27
0
1
Order By: Relevance
“…In this study there is no difference in female:male ratio, 1.1:1, observed in other African countries [14]. However Zanzibar, whose population partly has Arab ethnicity, had more female patients (62.3% female vs 37.7% male) which is in accordance to other Arab Countries [21] which differs from what is seen in several caucasian populations where T1D is slightly more common among boys <15 years of age and >15 years of age twice as common among males as among females. Of the children with documentation regarding family history of diabetes, 30.6% had first degree relatives which is 2-3 times more common than generally observed in western countries [1,2].…”
Section: Discussionsupporting
confidence: 76%
“…In this study there is no difference in female:male ratio, 1.1:1, observed in other African countries [14]. However Zanzibar, whose population partly has Arab ethnicity, had more female patients (62.3% female vs 37.7% male) which is in accordance to other Arab Countries [21] which differs from what is seen in several caucasian populations where T1D is slightly more common among boys <15 years of age and >15 years of age twice as common among males as among females. Of the children with documentation regarding family history of diabetes, 30.6% had first degree relatives which is 2-3 times more common than generally observed in western countries [1,2].…”
Section: Discussionsupporting
confidence: 76%
“…age group. Different studies showed variable prevalence of DKA among different countries ranging from 17% (Egypt) to 67% (Saudi Arabia) 22 24 that may be attributed to marked β cell damage and late diagnosis. However this is in sharp contrast to the SW lone findings from Pakistan who reported that more than one half (55.5%) of the children with DKA were older than 10 yrs.…”
Section: Discussionmentioning
confidence: 99%
“…The dissimilarity of PN among the different Arab countries possibly reflects the genetic and socioeconomic heterogeneity of the people in this Arab region. Further, differences in the methods of measuring the outcome between different studies could also associated with this heterogeneity [ 62 ].…”
Section: Complicationsmentioning
confidence: 99%